PPG Students’ Perceptions of Lecturer Competence in the In-Service PPG at the Teacher Education Institute (LPTK) of IAIN Pontianak: Cross-Sectional Quantitative Survey with PLS and Cronbach’s Alpha Validation - Sari, Nopita; Muthmainnah, Fitri; Juliansyah, Juliansyah; Izudin, Muhammad Irfan; Nelly, Nelly (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2025)
Purpose – To assess in-service Teacher Professional Education (Pendidikan Profesi Guru, PPG) students’ perceptions of lecturer competence in providing learning services in the in-service PPG program at the Teacher Education Institute (LPTK) of IAIN Pontianak. The research rationale refers to the demands of the 21st century, Technological Pedagogical Content Knowledge (TPACK), and the utilization of the Learning Management System (LMS). Design/methods/approach – Descriptive cross-sectional quantitative survey; 215 students were invited, 177 valid responses were analyzed (≈82,3%). Data were collected through a questionnaire. Descriptive analysis summarized domain scores; construct validity was evaluated with PLS (outer loadings ≥ 0,50) and reliability with Cronbach’s alpha (SPSS 22.0). Findings – All 27 items met the loading threshold. High reliability: pedagogical α=0,907 (9 items), professional α=0,888 (7), personality α=0,884 (6), social α=0,839 (5). Perceptions of lecturer competence “very good”: pedagogical 93,09%; professional 92,94%; personality 93,53%; social 93,08%. Item diagnostics highlighted areas for improvement: diversity of assessment, integration of research findings, consistency of words–actions, as well as lecturers’ closeness in recognizing students. Research implications – Program priorities: assessment literacy, research-based teaching, professional role modeling, and relational lecturer–student practices; calibration of assessment aligned with learning contracts/indicators; optimize the LMS so that the admin role is supportive, not substitutive.